Effects of pulmonary rehabilitation on daily life physical activity of fibrotic idiopathic interstitial pneumonia patients. Issue 2 (11th June 2018) - Wallaert, Benoit; Masson, Nicolas; Le Rouzic, Olivier; Chéhère, Baptiste; Wémeau-Stervinou, Lidwine; Grosbois, Jean-Marie
According to the international consensus statement of 2011, idiopathic pulmonary fibrosis (IPF) and idiopathic nonspecific interstitial pneumonia (NSIP) are classified as fibrotic idiopathic interstitial pneumonia (f-IIP) of unknown aetiology [1]. f-IIP patients display persistent and significant dyspnoea, exercise intolerance and poor health-related quality of life [2]. f-IIP is also associated with a marked reduction in daily life physical activity (DLPA ) [3], which is related to morbidity and mortality in many chronic diseases, including f-IIP [4–6]. Fibrotic idiopathic interstitial pneumonia patients derived benefit from a pulmonary rehabilitation programme in terms of exercise tolerance, anxiety, depression and quality of life without increasing their daily life physical activity http://ow.ly/WV7U30kgNkU